UNIVERSITY PUBLISHING CONCEPTS: PROBLEMS OF TERMINOLOGY - GALINIENĖ, GINTARĖ (Knygotyra, 2015)
By analyzing scientific literature on the subject of university publishing the following problems were discovered: first, the concept of university publishing is not used in Lithuanian book science in general, on the other hand, this term is not present in the Lithuanian language dictionaries or glossaries; third, a more general concept of academic publishing is often in use. Thus, the concept of university publishing is undefined. One can notice that the term of academic publishing is often used instead of the university publishing. By analyzing specific activity of university publishers it was discovered that essential meaning aspects of the terms are lost when using the generalized term of academic publishing. These aspects are very important for understanding and identification of essential features of the university publishing. The legitimizing of the concept of the university publishing will help to discuss and research the phenomena of the university publishing. The analysis of the definition of the term academic publishing has shown that this concept is wider and includes university publishing as a narrower concept. Therefore, it is possible to identify the types of academic publishing by subordination to a certain educational or research institutions. It would be important to emphasize the broadness and narrowness of the concepts academic and university publishing. The investigation of the usage of both terms in Lithuanian and foreign literature shows that the use of them depends on the traditions of understanding academic and university publishing in a particular country.